Fatal agricultural injuries in preschool children: risks, injury patterns and strategies for prevention - Brison, Robert J. (Canadian Medical Association, 2006)
BACKGROUND: Agricultural injuries are an important health concern for pediatric populations and particularly for children of pre school age. This study was conducted to estimate rates and determine patterns of fatal agricultural injury among young children exposed to agricultural hazards and to identify strategies to prevent such injuries. METHODS: A national case series was assembled retrospectively for the years 1990–2001. We identified children aged 1–6 years who were fatally injured during the course of agricultural work or through contact with a hazard of an agricultural worksite. Using a standardized survey instrument, we collected data from provincial coroners' and medical examiners' case files. Fatal agricultural injury rates (calculated with denominator data from the Canada Census of Agriculture) were compared with national all-cause, unintentional fatal injury rates in the general population of Canadian children during the same period (calculated with denominator data from the Canada Census of Population). RESULTS: The annual rate of fatal agricultural injury was substantially higher than that of all-cause, unintentional fatal injury among Canadian children aged 1–6 years (14.9 v. 8.7 per 100 000 person-years, respectively). Differences in risk were attributed to elevated fatal agricultural injury rates among boys. Most injuries occurred in the agricultural worksite, largely (84/115 [73%]) the result of 3 mechanisms: being run over by agricultural machinery as a bystander (29%) or as an extra rider who fell from the machine (22%), or asphyxia due to drowning (23%). Major crush injuries (of the head, chest and abdomen) and asphyxia from drowning were the most frequent mechanisms of injury. INTERPRETATION: Preschool-aged children exposed to agricultural worksites are at high risk of fatal injuries. Prevention strategies should focus on restricting children's access to these worksites. Physicians and allied health care professionals who care for rural families could take on a proactive role in communicating the nature and magnitude of these risks.